Do artificial income smoothing and real income smoothing contribute to firm value equivalently? - Huang, Pinghsun; Zhang, Yan; Deis, Donald R.; Moffitt, Jacquelyn S. (Journal of Banking & Finance, 2009)
This paper examines the potential impacts of artificial smoothing (abnormal accruals) and real smoothing (derivatives) on firm value. We find that the value of the firm decreases with the magnitude of abnormal accruals and increases with the level of derivative use. Moreover, the accrual discount is more pronounced in firms with weak investor protection and the hedging premium is greater for poorly governed firms. These results suggest that although managers can engage in real smoothing to improve the informativeness of firms’ earnings and thus reduce agency costs, they might use artificial techniques to cosmetically improve the income stream in order to expropriate minority shareholders. In further support of agency theories, we report that poor corporate governance motivates the use of abnormal accruals and discourages derivative use.